A ternary polymer donor material and its preparation and application
By introducing different contents of chloride pneumatic and fluoride pneumatic pneumatis in the polymer to the body, the regulating molecular grade with fluorine chlorine synergy is used to solve the polymer in the existing technology. The problem of factor and short -circuit current density achieves high -efficiency photoelectric conversion efficiency.
Patent Information
- Application Number
- CN202111669331.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-12-31
AI Technical Summary
While the existing polymer donor materials increase the open circuit voltage of the conjugated polymer, it is difficult to maintain high filling factor and short circuit current density, resulting in excessive driving force or excessive energy loss, making it difficult to achieve a balance between the two.
By introducing different contents of chloroneophyl perthine (BDT-2CL) and fluoride pneumatic (BDT-2F), the strategy of random co-agglomeration is used to design a gradient ternary cluster. , A balance between driving force and energy loss.
While improving the voltage of the co -pillar polymer, maintaining high -fill factor and short -circuit current density, significantly improved the optoelectronic conversion efficiency of organic solar cells.
Smart Images

Figure CN114437316B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic polymer photovoltaic devices or organic semiconductor thin film solar cells, specifically to the technical field of polymer donor materials, and in particular to a ternary polymer donor material and its preparation and application. Background Art
[0002] As one of the most promising candidate technologies for clean energy, polymer solar cells (PSCs) have attracted much attention in recent years due to their outstanding advantages such as light weight, strong flexibility, solution processability, and low production cost. Due to the development of organic photovoltaic materials and device engineering, many high-power conversion efficiency (PCE) polymer solar cells with excellent performance have been introduced. In the past few years, non-fullerene acceptor materials have shown strong light-harvesting ability and high photoelectric conversion efficiency, bringing PCE breakthroughs again and again. In addition, polymer donor materials, as an important component of the active layer family, also play a vital role in high-performance photovoltaic devices.
[0003] For efficient PSCs, polymer donor materials usually have the following intrinsic characteristics: (A) complementary light absorption with the acceptor to maximize the use of the spectrum; (B) suitable molecular energy levels between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) to match the molecular energy levels of the acceptor to provide sufficient driving force for exciton dissociation and minimize energy loss; (C) good compatibility with the acceptor to provide better interface contact and form a good phase morphology to ensure an effective path for charge separation. However, at present, it is often faced with the situation of excessive driving force or excessive energy loss, and it is difficult to achieve a balance between the two.
[0004] Based on these requirements, in the past decade, fluorination and chlorination strategies are often introduced in the design and synthesis of high-performance polymer materials to adjust the molecular energy level, expand absorption and optimize the phase state of polymer donor materials. Unlike fluorine (F) atoms, chlorine (Cl) atoms have empty 3D orbitals that can accept electron pairs or π-electrons to help delocalize electrons, so chlorination can effectively reduce the energy level, even more effectively than fluorination. However, chlorine atoms have a large atomic radius, which will lead to large steric hindrance, which may also destroy the planarity of conjugated polymers, thereby affecting the morphology and photovoltaic performance of polymer donor materials, especially the filling factor (FF) and short-circuit current density (J SC ). Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a ternary polymer donor material and its preparation and application, and to carry out reasonable structural design through fluorination and chlorination strategies, so as to improve the open circuit voltage of the conjugated polymer while maintaining a high filling factor and short-circuit current density of the ternary polymer donor material.
[0006] In order to achieve the above-mentioned and other related purposes, the first aspect of the present invention provides a ternary polymer donor material, the chemical structure of which is shown below:
[0007]
[0008] The molar weight of the x component in the donor material is 90-20%, and the molar weight of the y component in the donor material is 10-80%.
[0009] Furthermore, the molar proportions of the x component and the y component in the polymer donor material are 90%, 10%, or 80%, 20%, or 50%, 50%, or 20%, 80%, respectively. The above four polymer donor materials are named PM6.1, PM6.2, PM6.5, and PM6.8, respectively.
[0010] The second aspect of the present invention provides a method for preparing the ternary polymer donor material according to the first aspect, which is prepared by a Still cross-coupling reaction of a compound represented by formula (I), a compound represented by formula (II) and a compound represented by formula (III),
[0011]
[0012] Furthermore, the preparation method of the ternary polymer donor material comprises the following steps:
[0013] The compound represented by formula (I), the compound represented by formula (II) and the compound represented by formula (III) are dissolved in an organic solvent, a catalyst is added, and the mixture is heated and stirred under inert gas protection conditions to react. After the reaction is completed, the reaction liquid is separated and purified to obtain the ternary polymer donor material.
[0014] Furthermore, the molar ratio of compounds (I), (II) and (III) is (0.9-0.2):(0.1-0.8):1, preferably 0.9:0.1:1, 0.8:0.2:1, 0.5:0.5:1, 0.2:0.8:1.
[0015] Furthermore, the organic solvent is at least one of anhydrous and oxygen-free toluene, N,N-dimethylformamide, tetrahydrofuran, and anhydrous and oxygen-free chlorobenzene, preferably anhydrous and oxygen-free toluene.
[0016] Further, the catalyst is selected from a palladium catalyst, or the catalyst is selected from a combination of a palladium catalyst and a phosphorus catalyst, the palladium catalyst is selected from at least one of tris(dibenzylideneacetone)dipalladium, tetrakistriphenylphosphine palladium, bis(dibenzylideneacetone)palladium, and bis(triphenylphosphine)palladium dichloride, and the phosphorus catalyst is selected from tris(o-methylphenyl)phosphine.
[0017] Furthermore, the amount of the catalyst used is 2% to 20%, preferably 6 to 18%, of the total molar content of compounds (I), (II) and (III).
[0018] Furthermore, when the catalyst is selected from palladium catalyst, its usage is 8% to 10% of the total molar content of compounds (I), (II) and (III).
[0019] Furthermore, when the catalyst is selected from a combination of a palladium catalyst and a phosphorus catalyst, the amount of the palladium catalyst used is 4% to 12% of the total molar content of compounds (I), (II) and (III), and the amount of the phosphorus catalyst used is 2% to 6% of the total molar content of compounds (I), (II) and (III).
[0020] Furthermore, the heating and stirring reaction temperature is 100 to 120°C, preferably 110°C.
[0021] Furthermore, the heating and stirring reaction time is ≥ 0.2 hours, preferably 0.2 to 5 hours.
[0022] Furthermore, when the catalyst is selected from a palladium catalyst, the reaction time is 1 to 5 hours; when the catalyst is selected from a combination of a palladium catalyst and a phosphorus catalyst, the reaction time is 0.2 to 1 hour.
[0023] Furthermore, the number average molecular weight (M n ) is 10~50kDa.
[0024] Different reaction times and different catalysts can produce products with different molecular weights. When the catalyst is selected from a palladium catalyst, after 0.5 hours of reaction, the number average molecular weight (M n ) is 10 kDa; after 1 hour of reaction, the number average molecular weight (M n ) is 15.0 kDa; after 2 hours of reaction, the number average molecular weight (M n ) is 30.0 kDa; after 5 hours of reaction, the number average molecular weight (M n ) is 50.0 kDa.
[0025] When the catalyst is selected from a combination of a palladium catalyst and a phosphorus catalyst, after 0.2 hours of reaction, the number average molecular weight (Mn ) is 5 kDa; after 0.5 hours of reaction, the number average molecular weight (M n ) is 15 kDa; after 0.7 hours of reaction, the number average molecular weight (M n ) is 30 kDa; after 1 hour of reaction, the number average molecular weight (M n ) is 50kDa.
[0026] Furthermore, the inert gas is selected from any one of nitrogen and argon.
[0027] Furthermore, the reaction liquid separation and purification method is as follows: after the reaction is completed, the heating is stopped, and the reaction system is cooled to room temperature, and the reaction liquid is poured into methanol to precipitate a solid precipitate, and the precipitate is collected by filtration, and the solid precipitate is extracted with methanol, acetone, and n-hexane in sequence using a Soxhlet extractor to remove small molecular weight products, and finally extracted with chloroform until the solution in the Soxhlet extractor is colorless, and the chloroform solvent of the extraction is removed by rotary evaporation to obtain a crude product, and the crude product is separated by silica gel column chromatography to obtain a ternary polymer donor material with uniform molecular weight distribution.
[0028] Furthermore, in the reaction liquid separation and purification method, the amount of methanol used is more than 20 times the volume of the reaction liquid.
[0029] Furthermore, in the reaction solution separation and purification method, the solid precipitate is extracted with methanol, acetone, and n-hexane in sequence using a Soxhlet extractor for 10 to 15 hours, preferably 12 hours.
[0030] Furthermore, in the reaction solution separation and purification method, the crude product is chromatographed on a 100-200 mesh silica gel column using pure chloroform as the eluent.
[0031] The third aspect of the present invention provides use of the ternary polymer donor material according to the first aspect or the ternary polymer donor material prepared according to the method described in the second aspect in the preparation of an organic polymer photovoltaic device or an organic solar cell.
[0032] The fourth aspect of the present invention provides an organic solar cell device, comprising the ternary polymer donor material according to the first aspect or the ternary polymer donor material prepared according to the method described in the second aspect.
[0033] Furthermore, the organic solar cell device further comprises an acceptor material, and the acceptor material is selected from any one of Y6, N3, and BTP-eC9.
[0034] Furthermore, the organic solar cell device further comprises a positive electrode material, and the positive electrode material is selected from ITO (indium tin oxide).
[0035] Furthermore, the organic solar cell device also includes an anode modification layer (i.e., a hole transport layer), and the anode modification layer material is selected from PEDOT:PSS, PEDOT is a polymer of EDOT (3,4-ethylenedioxythiophene monomer), i.e., poly(3,4-ethylenedioxythiophene), and PSS is polystyrene sulfonate.
[0036] Furthermore, the organic solar cell device further comprises a cathode modification layer (ie, an electron transport layer), and the cathode modification layer material is selected from Phen-NaDPO.
[0037] Furthermore, the organic solar cell device further comprises a cathode, and the cathode material is selected from Ag.
[0038] Furthermore, the organic solar cell device adopts an upright device structure.
[0039] As described above, the ternary polymer donor material of the present invention and its preparation and application have the following beneficial effects:
[0040] The present invention introduces different contents of chlorinated thiophene (BDT-2Cl) and fluorinated thiophene (BDT-2F) for the first time, and adopts a random copolymerization strategy to design and synthesize a gradient ternary copolymer. The ternary copolymer synthesized by the present invention is a ternary polymer donor material based on the synergistic effect of fluorine and chlorine. By regulating the molecular energy level of chlorinated thiophene (BDT-2Cl), a gradient voltage change is exhibited, and a balance between driving force and energy loss is achieved through the synergistic effect of fluorine and chlorine. At the same time, the ternary polymer donor material of the present invention also has excellent semiconductor properties, good self-assembly and solution processability. The photoelectric conversion efficiency of the organic solar cell prepared therefrom is significantly improved, and it has great application potential and value in the field of photovoltaic devices such as organic solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Shown is a schematic diagram of the synthesis route of the ternary polymer donor material of the present invention.
[0042] Figure 2 Shown are the molecular structures of materials Y6, Y6, PEDOT, PSS, and Phen-NaDPO used in the present invention.
[0043] Figure 3 Shown is a schematic structural diagram of an organic solar cell device prepared in the present invention.
[0044] Figure 4 The devices in Example 2 (PM6.1: Y6), Example 3 (PM6.2: Y6), Example 4 (PM6.5: Y6) and Example 5 (PM6.8: Y6) of the present invention are shown under standard test conditions (AM1.5, 100 mW / cm2 )'s current density-voltage characteristic (JV) curve.
[0045] Figure 5 The devices in Example 2 (PM6.1: Y6), Example 3 (PM6.2: Y6), Example 4 (PM6.5: Y6) and Example 5 (PM6.8: Y6) of the present invention are shown under standard test conditions (AM1.5, 100 mW / cm 2 )’s external quantum efficiency (EQE) curve. DETAILED DESCRIPTION
[0046] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0047] The present invention provides a ternary polymer donor material based on the synergistic effect of fluorine and chlorine, and its chemical structure is as follows:
[0048]
[0049] The molar weight of the x component in the donor material is 90-20%, and the molar weight of the y component in the donor material is 10-80%.
[0050] Furthermore, the molar proportions of the x component and the y component in the polymer donor material are 90%, 10%, or 80%, 20%, or 50%, 50%, or 20%, 80%, respectively. The above four polymer donor materials are named PM6.1, PM6.2, PM6.5, and PM6.8, respectively.
[0051] The ternary polymer donor material provided by the present invention is prepared by a Still cross-coupling reaction of a compound represented by formula (I), a compound represented by formula (II) and a compound represented by formula (III).
[0052]
[0053] Specifically, the preparation method of the ternary polymer donor material of the present invention comprises the following steps:
[0054] (1) dissolving the compound represented by formula (I), the compound represented by formula (II) and the compound represented by formula (III) in an organic solvent, adding a catalyst, and heating and stirring to react under inert gas protection;
[0055] (2) Separation and purification of the reaction solution: After the reaction is completed, the heating is stopped. When the reaction system is cooled to room temperature, the reaction solution is poured into methanol (using methanol that is 20 times the volume of the reaction solution) to precipitate a solid precipitate. The precipitate is collected by filtration. The solid precipitate is extracted with methanol, acetone, and n-hexane using a Soxhlet extractor for 10 to 15 hours each to remove low molecular weight products. Finally, it is extracted with chloroform until the solution in the Soxhlet extractor is colorless. The chloroform solvent is removed by rotary evaporation to obtain a crude product. The crude product is chromatographed on a small amount of 100-200 mesh silica gel column with pure chloroform as the eluent. The column is separated and the effluent components are collected to obtain a terpolymer donor material with uniform molecular weight distribution.
[0056] The molar ratio of compounds (I), (II) and (III) is (0.9-0.2): (0.1-0.8): 1. By controlling the molar ratio of the introduced compound (II) and regulating its content, a series of polymer materials PM6.1, PM6.2, PM6.5 and PM6.8 are obtained. When preparing PM6.1, the molar ratio of compounds (I), (II) and (III) is 0.9:0.1:1; when preparing PM6.2, the molar ratio of compounds (I), (II) and (III) is 0.8:0.2:1; when preparing PM6.5, the molar ratio of compounds (I), (II) and (III) is 0.5:0.5:1; when preparing PM6.8, the molar ratio of compounds (I), (II) and (III) is 0.2:0.8:1.
[0057] The organic solvent is at least one of anhydrous and oxygen-free toluene, N,N-dimethylformamide, tetrahydrofuran, and anhydrous and oxygen-free chlorobenzene, preferably anhydrous and oxygen-free toluene.
[0058] Wherein, the catalyst is selected from a palladium catalyst, or the catalyst is selected from a combination of a palladium catalyst and a phosphorus catalyst, the palladium catalyst is selected from at least one of tris(dibenzylideneacetone)dipalladium, tetrakistriphenylphosphine palladium, bis(dibenzylideneacetone)palladium, and bis(triphenylphosphine)palladium dichloride, and the phosphorus catalyst is selected from tris(o-methylphenyl)phosphine.
[0059] Wherein, the amount of the catalyst is 2% to 20% of the total molar content of compounds (I), (II) and (III), preferably 6% to 18%. More preferably, when the catalyst is selected from a palladium catalyst, the amount thereof is 8% to 10% of the total molar content of compounds (I), (II) and (III); when the catalyst is selected from a combination of a palladium catalyst and a phosphorus catalyst, the amount of the palladium catalyst is 4% to 12% of the total molar content of compounds (I), (II) and (III), and the amount of the phosphorus catalyst is 2% to 6% of the total molar content of compounds (I), (II) and (III).
[0060] The heating and stirring reaction temperature is 100-120°C, preferably 110°C.
[0061] The heating and stirring reaction time is ≥ 0.2 hours, preferably 0.2 to 5 hours. More preferably, when the catalyst is a palladium catalyst, the reaction time is 1 to 3 hours; when the catalyst is a combination of a palladium catalyst and a phosphorus catalyst, the reaction time is 0.5 to 1 hour.
[0062] Different reaction times and different catalysts can produce products with different molecular weights. When the catalyst is selected from a palladium catalyst, after 0.5 hours of reaction, the number average molecular weight (M n ) is 10 kDa; after 1 hour of reaction, the number average molecular weight (M n ) is 15.0 kDa; after 2 hours of reaction, the number average molecular weight (M n ) is 30.0 kDa; after 5 hours of reaction, the number average molecular weight (M n ) is 50.0 kDa.
[0063] When the catalyst is selected from a combination of a palladium catalyst and a phosphorus catalyst, after 0.2 hours of reaction, the number average molecular weight (M n ) is 5 kDa; after 0.5 hours of reaction, the number average molecular weight (M n ) is 15 kDa; after 0.7 hours of reaction, the number average molecular weight (M n ) is 30 kDa; after 1 hour of reaction, the number average molecular weight (M n ) is 50kDa.
[0064] Wherein, the inert gas is selected from any one of nitrogen and argon.
[0065] The present invention also provides an organic solar cell device prepared by using the ternary polymer donor material as an active layer donor material. Specifically, the organic solar cell device of the present invention preferably adopts an upright device structure: ITO / PEDOT:PSS / donor:PYSe-2FT / Phen-NaDPO / Ag, and its structure is as follows: Figure 3As shown, the positive electrode material is Indiumtin oxide (ITO), which is a transparent conductive glass for the anode; the anode modification layer (i.e., the hole transport layer) is poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS); the active layer donor material (Donor) is any one of PM6.1, PM6.2, PM6.5, and PM6.8; the active layer acceptor material is Y6; the cathode modification layer (i.e., the electron transport layer) is phenyl(2-naphthyl)diphenylphosphine oxide (Phen-NaDPO, DPO); and the negative electrode material (cathode material) is Ag.
[0066] The chemical structures of Y6, PEDOT, PSS, and Phen-NaDPO are as follows Figure 2 The method for preparing the organic solar cell device provided by the present invention is as follows:
[0067] a) Cleaning the ITO glass: Use deionized water, acetone, and isopropanol to clean the ITO glass by ultrasonic cleaning for 30 minutes each, and then treat it in an ozone cleaning machine for 30 minutes;
[0068] b) Spin coating a hole transport layer PEDOT:PSS on the ITO glass with a thickness of 10-30 nm. The hole transport layer in the following examples has a thickness of 30 nm, and then performing a thermal annealing treatment in air.
[0069] c) In a glove box filled with nitrogen, the active layer mixed solution donor:Y6 is spin-coated on the hole transport layer PEDOT:PSS by solution method, and the mass ratio of donor to Y6 is 1:1.2. The specific method is: donor:Y6 is dissolved in chlorobenzene or chloroform at a concentration of 17 mg / mL; the active layer is spin-coated with a thickness of 80 to 300 nm, and the active layer in the following examples is 150 nm.
[0070] d) Spin-coat a Phen-NaDPO isopropanol solution on the active layer to prepare an electron transport layer with a thickness of 10 to 50 nm. The thickness of the electron transport layer in the following examples is 30 nm.
[0071] e) A metal silver electrode is evaporated on the Phen-NaDPO electron transport layer with a thickness of 90-100 nm. The thickness of the cathode in the following examples is 100 nm.
[0072] The raw material compounds, organic solvents, catalysts, electrode materials, modification layer materials, etc. used in the present invention can be directly purchased from the market.
[0073] The methods not described in detail in the present invention are all conventional methods in the art.
[0074] The following specific examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to specifically illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range according to the description herein, and are not limited to the specific values exemplified below.
[0075] Example 1
[0076] Preparation of ternary polymer donor materials
[0077] according to Figure 1 The synthetic route shown is used to prepare the ternary polymer donor material, and the process is as follows:
[0078] (1) Still cross-coupling reaction: The compound represented by formula (I), the compound represented by formula (II) and the compound represented by formula (III) are dissolved in an organic solvent, and different catalyst systems may be added, and heated, stirred and refluxed at 110°C under nitrogen protection. The organic solvent is anhydrous and oxygen-free toluene; when the catalyst system is tetrakistriphenylphosphine palladium, its dosage is 10% of the total molar content of compounds (I), (II) and (III), and the reaction time is 1 to 3 hours; when the catalyst system is a mixed catalyst of tris(o-methylphenyl)phosphine (molar weight of 8%) and tris(dibenzylideneacetone)dipalladium (molar weight of 4%), its dosage is 8% and 4% of the total molar content of compounds (I), (II) and (III), respectively, and the reaction time is 0.5 to 1 hour.
[0079] (2) Separation and purification of the reaction solution: After the reaction is completed, the heating is stopped, and the reaction system is cooled to room temperature, and then the reaction solution is poured into methanol (using methanol that is 20 times the volume of the reaction solution) to precipitate a solid precipitate, which is filtered and collected. The solid precipitate is extracted with methanol, acetone, and n-hexane in sequence using a Soxhlet extractor for 12 hours to remove small molecular weight products, and finally extracted with chloroform until the solution in the Soxhlet extractor is colorless, and the chloroform solvent is removed by rotary evaporation to obtain a crude product. The crude product is chromatographed on a small amount of 100-200 mesh silica gel column with pure chloroform as the eluent, and the effluent components are collected to obtain the polymer donors PM6.1, PM6.2, PM6.5, and PM6.8 with uniform molecular weight distribution.
[0080] As shown in Table 1, by controlling the molar ratio of the introduced compounds I and II to regulate their contents, a series of polymer materials with a number average molecular weight (M n) respectively PM6.1: (M n =28.32kDa), PM6.2: (M n =31.28kDa), PM6.5: (M n =30.17 kDa), PM6.8: (M n =35.80 kDa), where M n This is the test result of high temperature gel chromatography (GPC).
[0081] Table 1
[0082] Donor material name The proportion of x component The proportion of y component PM6 100% 0% PM6.1 90% 10% PM6.2 80% 20% PM6.5 50% 50% PM6.8 20% 80% PM7 0% 100%
[0083] Polymers PM6 and PM7 were purchased directly from the market, and their characterization data are as follows:
[0084] PM6: (M n =29.38 kDa)
[0085] 1 H NMR (400MHz, CDCl3), 6.95~7.1(d,1H,=CH-), 3.5~3.65(m,12H,CH2), 2.84~2.99(m,10H,CH2), 1.57~1.98(m,12H,CH3), 0.66~1.54(m,32H,CH2 and CH3);
[0086] Elemental analysis (%) Theoretical value: C = 67.27%, H = 6.61%, S = 20.52%. Test value: C = 67.47%, H = 6.33%, S = 20.92%.
[0087] PM7: (M n =40.23 kDa)
[0088] 1 H NMR (400MHz, CDCl3), δ7.45~7.65(s,4H,=CH-), 3.5~3.65(m,10H,CH2), 2.84~2.99(m,14H,CH2), 1.57~1.98(m,16H,CH3), 0.66~1.54(m,36H,CH2 and CH3);
[0089] Elemental analysis (%) Theoretical value: C = 65.54%, H = 6.44%, S = 19.99%. Test value: C = 65.12%, H = 6.40%, S = 20.16%.
[0090] The characterization data of the ternary polymers PM6.1, PM6.2, PM6.5, and PM6.8 are as follows:
[0091] PM6.1: (M n =28.32 kDa)
[0092] 1 H NMR (400MHz, CDCl3) δ7.45~7.65(s,1H,=CH-), 6.95~7.1(d,9H,=CH-), 3.5~3.65(m, 15H,CH2),2.84~2.99(m,34H,CH2),1.57~1.98(m,10H,CH3),0.66~1.54(m,40H,CH2 and CH3);
[0093] Elemental analysis (%) Theoretical value: C = 66.81%, H = 6.38%, S = 20.86%. Test value: C = 66.37%, H = 6.25%, S = 20.77%.
[0094] PM6.2: (M n =31.28 kDa)
[0095] 1 H NMR (400MHz, CDCl3) δ7.45~7.65(s,1H,=CH-), 6.95~7.1(d,4H,=CH-), 3.5~3.65(m ,8H,CH2),2.84~2.99(m,18H,CH2),1.57~1.98(m,5H,CH3),0.66~1.54(m,52H,CH2 and CH3);
[0096] Elemental analysis (%) Theoretical value: C = 66.62%, H = 6.38%, S = 20.80%. Test value: C = 66.20%, H = 6.33%, S = 20.92%.
[0097] PM6.5: (M n =30.17 kDa)
[0098] 1 H NMR (400MHz, CDCl3) δ7.45~7.65(s,1H,=CH-), 6.95~7.1(d,1H,=CH-), 3.5~3.65(m,1 6H,CH2),2.84~2.99(m,33.5H,CH2),1.57~1.98(m,12H,CH3),0.66~1.54(m,38H,CH2 and CH3);
[0099] Elemental analysis (%) Theoretical value: C = 66.23%, H = 6.63%, S = 20.50%. Test value: C = 66.16%, H = 6.83%, S = 20.32%.
[0100] PM6.8: (M n =35.80 kDa)
[0101] 1 H NMR (400MHz, CDCl3) δ7.45~7.65(s,4H,=CH-), 6.95~7.1(d,1H,=CH-), 3.5~3.65(m ,8H,CH2),2.84~2.99(m,18H,CH2),1.57~1.98(m,6H,CH3),0.66~1.54(m,54H,CH2 and CH3);
[0102] Elemental analysis (%) Theoretical value: C = 65.57%, H = 6.27%, S = 20.47%. Test value: C = 65.37%, H = 6.40%, S = 20.81%.
[0103] Example 2
[0104] PM6.1:Y6 organic solar cell device preparation
[0105] The substrate composed of the transparent substrate layer and the transparent conductive electrode ITO was ultrasonically cleaned with a cleaning solution, deionized water, acetone and isopropanol, respectively, and then dried with nitrogen. After the substrate was placed in an ozone cleaning machine for 30 minutes, the hole transport layer material PEDOT:PSS was spin-coated in air (4000rpm, 20s), and then thermally annealed in air (150°C, 10min). The sample was then transferred into a glove box filled with nitrogen, and an active layer (PM6.1:Y6=1:1.2, 17mg mL -1 , chloroform as solvent, rotation speed of 3200 rpm, 0.5% vol chloronaphthalene additive (CN), thermal annealing at 100°C for 10 minutes after spin coating the active layer; then spin coating the electron transport layer DPO on the active layer (2000 rpm, 20s), and then evaporate Ag electrode (100 nm) on the electron transport layer to obtain a PM6.1:Y6 organic solar cell device.
[0106] Example 3
[0107] PM6.2:Y6 organic solar cell device preparation
[0108] The substrate composed of the transparent substrate layer and the transparent conductive electrode ITO was ultrasonically cleaned with a cleaning solution, deionized water, acetone and isopropanol, respectively, and then dried with nitrogen. After the substrate was placed in an ozone cleaning machine for 30 minutes, the hole transport layer material PEDOT:PSS was spin-coated in air (4000rpm, 20s), and then thermally annealed in air (150°C, 10min). The sample was then transferred into a glove box filled with nitrogen, and an active layer (PM6.2:Y6=1:1.2, 17mg mL -1 , chloroform as solvent, rotation speed of 3200rpm, 0.5%vol of chloronaphthalene additive (CN), after spin coating the active layer, thermal annealing was performed at 100°C for 10 minutes, and then Ag electrode (100nm) was evaporated on the electron transport layer to obtain PM6.2:Y6 organic solar cell device.
[0109] Example 4
[0110] PM6.5:Y6 organic solar cell device preparation
[0111] The substrate composed of the transparent substrate layer and the transparent conductive electrode ITO was ultrasonically cleaned with a cleaning solution, deionized water, acetone and isopropanol, respectively, and then dried with nitrogen. After the substrate was placed in an ozone cleaning machine for 30 minutes, the hole transport layer material PEDOT:PSS was spin-coated in air (4000rpm, 20s), and then thermally annealed in air (150°C, 10min). The sample was then transferred into a glove box filled with nitrogen, and an active layer (PM6.5:Y6=1:1.2, 17mg mL -1 , chloroform as solvent, rotation speed of 3200 rpm, 0.5% vol chloronaphthalene additive (CN), thermal annealing at 100°C for 10 minutes after spin coating the active layer; then spin coating the electron transport layer DPO on the active layer (2000 rpm, 20s), and then evaporate Ag electrode (100 nm) on the electron transport layer to obtain a PM6.5:Y6 organic solar cell device.
[0112] Example 5
[0113] PM6.8:Y6 organic solar cell device preparation
[0114] The substrate composed of the transparent substrate layer and the transparent conductive electrode ITO was ultrasonically cleaned with a cleaning solution, deionized water, acetone and isopropanol, respectively, and then dried with nitrogen. After the substrate was placed in an ozone cleaning machine for 30 minutes, the hole transport layer material PEDOT:PSS was spin-coated in air (4000rpm, 20s), and then thermally annealed in air (150°C, 10min). The sample was then transferred into a glove box filled with nitrogen, and an active layer (PM6.1:Y6=1:1.2, 17mg mL -1 , chloroform as solvent, rotation speed of 3200 rpm, 0.5% vol chloronaphthalene additive (CN), thermal annealing at 100°C for 10 minutes after spin coating the active layer; then spin coating the electron transport layer DPO on the active layer (2000 rpm, 20s), and then evaporate Ag electrode (100 nm) on the electron transport layer to obtain PM6.8:Y6 organic solar cell device.
[0115] Example 6
[0116] PM6:Y6 organic solar cell device preparation
[0117] The substrate composed of the transparent substrate layer and the transparent conductive electrode ITO was ultrasonically cleaned with a cleaning solution, deionized water, acetone and isopropanol, respectively, and then dried with nitrogen. After the substrate was placed in an ozone cleaning machine for 30 minutes, the hole transport layer material PEDOT:PSS was spin-coated in air (4000rpm, 20s), and then thermally annealed in air (150°C, 10min). The sample was then transferred into a glove box filled with nitrogen, and an active layer (PM6:Y6=1:1.2, 17mg mL -1 , chloroform as solvent, rotation speed of 3200 rpm, 0.5% vol chloronaphthalene additive (CN), thermal annealing at 100°C for 10 minutes after spin coating the active layer; then spin coating the electron transport layer DPO on the active layer (2000 rpm, 20s), and then evaporate Ag electrode (100 nm) on the electron transport layer to obtain PM6:Y6 organic solar cell device.
[0118] Example 7
[0119] PM7:Y6 organic solar cell device preparation
[0120] The substrate composed of the transparent substrate layer and the transparent conductive electrode ITO was ultrasonically cleaned with a cleaning solution, deionized water, acetone and isopropanol, respectively, and then dried with nitrogen. After the substrate was placed in an ozone cleaning machine for 30 minutes, the hole transport layer material PEDOT:PSS was spin-coated in air (4000rpm, 20s), and then thermally annealed in air (150°C, 10min). The sample was then transferred into a glove box filled with nitrogen, and an active layer (PM7:Y6=1:1.2, 17mg mL -1 , chloroform as solvent, rotation speed of 3200 rpm, 0.5% vol chloronaphthalene additive (CN), thermal annealing at 100°C for 10 minutes after spin coating the active layer; then spin coating the electron transport layer DPO on the active layer (2000 rpm, 20s), and then evaporate Ag electrode (100 nm) on the electron transport layer to obtain PM7:Y6 organic solar cell device.
[0121] In Examples 2 to 7, the effective thickness of the active layer was tested by a step profiler, and the effective area of the device was 0.08636 cm 2 .
[0122] In standard sunlight (AM 1.5G, light intensity 100mW cm -2 ) under irradiation conditions, the performance of the devices in Examples 2 to 5 was tested using a computer-controlled Keithley 2400 digital source meter. The current density-voltage (JV) curves of the devices are shown in FIG. Figure 4 As shown, the EQE curve of the device tested using the external quantum efficiency tester (Beijing Zhuoli Hanguang Instrument Co., Ltd., Solar Cell Scan100) is as follows Figure 5 The photovoltaic performance parameters are listed in Table 2.
[0123] Table 2. Photovoltaic performance parameters of organic solar cell devices in Examples 2 to 7
[0124] Active layer <![CDATA[V OC [mV]]]> <![CDATA[J SC [mA cm -2 ]]> FF[%] <![CDATA[PCE Max [%]]]> <![CDATA[PCE Ave [%]]]> <![CDATA[EQE[mA cm -2 ]]]> PM6.1:Y6 0.843 25.29 71.5 15.27 15.17±0.1 24.62 PM6.2:Y6 0.851 25.78 73.5 16.13 16.03±0.1 25.20 PM6.5:Y6 0.855 24.37 68.6 14.29 14.09±0.2 23.76 PM6.8:Y6 0.865 23.25 58.22 11.71 11.41±0.3 23.27 PM6:Y6 0.842 25.41 72.9 15.56 15.35±0.2 24.92 PM7:Y6 0.885 24.26 54.6 13.36 13.16±0.2 23.91
[0125] Figure 5 The external quantum efficiency (EQE) curves of the solar cell devices of Examples 2 to 5 are shown in FIG. 1 , which have a wide photocurrent response from 300 nm to 1000 nm. Figure 5It can be seen that the external quantum efficiency of the device based on PM6.2:Y6 is slightly higher than that of the devices based on PM6.1:Y6, PM6.5:Y6 and PM6.8:Y6, indicating that the ratio of the number of electrons collected by the device based on PM6.2:Y6 to the number of incident photons is higher than that of the devices based on PM6.1:Y6, PM6.5:Y6 and PM6.8:Y6. By integrating the EQE curve, the J of the post-processing device based on PM6.1:Y6, PM6.2:Y6, PM6.5:Y6 and PM6.8:Y6 is calculated. SC The values are 24.62 mA·cm -2 ,25.20mA·cm -2 and 23.76 mA cm -2 ,23.27mA·cm -2 , compared with the values obtained by the JV curve, their errors are all within 5%. The above results show that by regulating the content of chlorinated thiophene (BDT-Cl), the molecular energy level can be effectively regulated, and finally a gradient voltage change is exhibited. Under the condition of similar molecular weight, PM6.2:Y6 exhibits the best device performance of 16.13%, and finds the best balance point of fluorine-chlorine synergy, that is, the device battery composed of 20% BDT-2Cl and 80% fluorinated thiophene (2BDT-2F) is introduced to achieve a balance between driving force and energy loss.
[0126] At the same time, the photoelectric conversion efficiency of PM6.2:Y6 devices is improved compared with those made based on commercial materials PM6:Y6 and PM7:Y6. This shows that the polymer donor material prepared by the synergistic effect of fluorine and chlorine can effectively improve device performance and has great potential for commercial application.
[0127] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. An organic solar cell device, characterized in that: It includes a ternary polymer donor material and an acceptor material, and the chemical structural formula of the ternary polymer donor material is as follows: The molar weight of the x component in the donor material is 80%, and the molar weight of the y component in the donor material is 20%; the number average molecular weight of the ternary polymer donor material is 31.28 kDa; The acceptor material is Y6.
Citation Information
Patent Citations
Chlorinated benzodithiophene-based polymers for electronic and photonic applications
CN111278888A